Does succession run towards potential natural vegetation? An analysis across seres. (29th February 2016) - Prach, Karel; Tichý, Lubomír; Lencová, Kamila; Adámek, Martin; Koutecký, Tomáš; Sádlo, Jiří; Bartošová, Alena; Novák, Jan; Kovář, Pavel; Jírová, Alena; Šmilauer, Petr; Řehounková, Klára
Abstract: Questions: (1) Do 17 seres studied proceed towards corresponding potential natural vegetation; (2) what are the similarities between seral and potential natural vegetation, and is it possible to estimate how long it takes to reach potential natural vegetation; and (3) do primary and secondary seres differ? Location: Extracted peatlands, corridors of the former iron curtain, artificial fishpond islands and barriers, sedimentary basins, various spoil heaps after mining, various stone quarries, forest clearings, burned‐down forests, road verges, sand and gravel‐sand pits, river gravel bars and abandoned arable fields located in various parts of the Czech Republic. Methods: Seral stages were sampled by phytosociological relevés (2602). The following categories of successional age were considered: early (1–10 yrs), intermediate (11–25 yrs) and late (>25 yrs). Phytosociological relevés (386) representing corresponding potential natural vegetation were extracted from the National Phytosociological Database. DCA and CCA ordinations were performed to compare the pattern of seral stages with potential natural vegetation and between primary and secondary seres. Dissimilarity between seral stages of primary and secondary successions and the corresponding potential natural vegetation was further assessed using the Bray‐Curtis dissimilarity measure. Extrapolation was performed to estimate when the seres will reach the stage corresponding to potential natural vegetation. Results: The ordination showed that successions proceeded towards the corresponding potential natural vegetation and reflected substrate pH, site moisture and successional age. The estimated average time needed to reach potential natural vegetation was about 180 yrs for primary successions and about 260 yrs for secondary successions, considering presence–absence species data, and 200 and 250 yrs, respectively, considering cover data. All species recorded in potential natural vegetation (421) were also recorded in seral vegetation. Conclusions: In the general view across the high number of seres spread over the whole country, successions advanced in the direction of the corresponding potential natural vegetation. The extrapolated recovery of potential natural vegetation is faster in primary seres than in secondary ones, and seres sooner resemble the corresponding potential natural vegetation in species composition than in vegetation structure. Abstract : Successions proceeded towards the corresponding potential natural vegetation and reflected substrate pH, site moisture and successional age, considering the high number (17) of seres spread over the whole country (Czech Republic). All species recorded in potential natural vegetation (421) were also recorded in seral vegetation.